2009
DOI: 10.1144/1354-079309-814
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of thermal conductivity of sedimentary rocks and the significance for basin temperature history

Abstract: Thermal history is an important control on generation of gas and oil in source rocks. Therefore, a realistic treatment of thermal conductivity in rocks is essential for hydrocarbon generation modelling in sedimentary basins. We present two different techniques for thermal conductivity estimation: (1) upscaling, based on arithmetic, geometrical and harmonic mean values of averaged conductivity from anticipated mineral composition; (2) infometric regression of thermal conductivity and anisotropy from measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…There are several ways to determine the thermal conductivity structure of the sediments in a basin, and the results will vary signi¢cantly depending on which model is applied. Fjeldskaar et al (2009) showed that thermal conductivities based on measured samples from the North Sea show signi¢cantly higher temperatures than mixing law models, and that this may be due to the fact that these models do not take into consideration the e¡ect of the texture of the sediments.…”
Section: Palaeotemperature and Hydrocarbon Maturationcontrasting
confidence: 67%
See 3 more Smart Citations
“…There are several ways to determine the thermal conductivity structure of the sediments in a basin, and the results will vary signi¢cantly depending on which model is applied. Fjeldskaar et al (2009) showed that thermal conductivities based on measured samples from the North Sea show signi¢cantly higher temperatures than mixing law models, and that this may be due to the fact that these models do not take into consideration the e¡ect of the texture of the sediments.…”
Section: Palaeotemperature and Hydrocarbon Maturationcontrasting
confidence: 67%
“…Fjeldskaar et al (2009) showed that thermal conductivities based on measured samples from the North Sea show significantly higher temperatures than mixing law models, and that this may be due to the fact that these models do not take into consideration the effect of the texture of the sediments. Since the variations between the different mixing law models have been thoroughly described by Fjeldskaar et al (2009), this is not tested in the present study, but this issue should also be considered when evaluating the temperature history of a sedimentary basin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermal conductivity depends on mineralogy and increases with sediment depth due to compaction and cementation (Wallmann et al, 2012). Considering a thermal conductivity of 0.9-3 W m −1 K −1 for clays (Fjeldskaar et al, 2009), 0.6 W m −1 K −1 for pore water in marine sediments (e.g. Deming et al, 1989), and an average porosity of 0.5 over the sediment column, the thermal conductivity of sediments was estimated at 0.7-1.34 W m −1 K −1 .…”
Section: Thickness Of the Gas Hydrate Stability Zonementioning
confidence: 99%